The Influence of The Kind of Feeding on The Average of Body Growth for The Infant of The Age (3-6) Months in Baghdad.City (Baghdad Science Journal, 2007)
This paper was conducted to identifying the body growth averages for the infants of the age (3-6) months and their relation with brest (natural ) or artificial feeding The results showed that the higher percentage was for the infants with the natural feeding in comparison with those of the artificial or mixed feeding. Also there was a clear increase in the average of the body growth for those with the natural feeding and such results were closer to the standard criterion. While the averages of body growth for those with the artificial or mixed feeding were low. In addition, it was clear that the averages of body growth of the infants with natural feeding and having home-made food were higher than those with the artificial feeding and having ready-made food. Therefore, it is important to add additional and complementary food for the infant and from the fourth month of the infant's age to ensure the sound continuity of the infant's growth. Such types of food are not necessarily ready-made or bought from the markets, they can be simple and home-made.